2021
DOI: 10.3389/fcell.2021.655731
|View full text |Cite
|
Sign up to set email alerts
|

The mTOR–Autophagy Axis and the Control of Metabolism

Abstract: The mechanistic target of rapamycin (mTOR), master regulator of cellular metabolism, exists in two distinct complexes: mTOR complex 1 and mTOR complex 2 (mTORC1 and 2). MTORC1 is a master switch for most energetically onerous processes in the cell, driving cell growth and building cellular biomass in instances of nutrient sufficiency, and conversely, allowing autophagic recycling of cellular components upon nutrient limitation. The means by which the mTOR kinase blocks autophagy include direct inhibition of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
120
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(146 citation statements)
references
References 94 publications
1
120
0
Order By: Relevance
“…mTOR is a serine/threonine kinase and an important cell regulator, which can regulate cell growth and proliferation in response to a variety of signals, and it plays an especially vital role in regulating autophagy [ 44 ]. mTOR is a highly evolved kinase whose catalytic core is composed of two different complexes, mTORC1 and mTORC2 [ 45 ]. Yu et al (2021) found that Qingfei oral liquid (QF) could participate in the regulation of autophagy through the mTOR signaling pathway to reduce the inflammation caused by respiratory syncytial virus (RSV) infection in asthmatic mice [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…mTOR is a serine/threonine kinase and an important cell regulator, which can regulate cell growth and proliferation in response to a variety of signals, and it plays an especially vital role in regulating autophagy [ 44 ]. mTOR is a highly evolved kinase whose catalytic core is composed of two different complexes, mTORC1 and mTORC2 [ 45 ]. Yu et al (2021) found that Qingfei oral liquid (QF) could participate in the regulation of autophagy through the mTOR signaling pathway to reduce the inflammation caused by respiratory syncytial virus (RSV) infection in asthmatic mice [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mTORC1 pathway plays a central role in the regulation of growth and metabolism in eukaryotic cells, affecting anabolism, autophagy and catabolism. 44 In addition, mTORC1 can also regulate mitochondrial metabolism, standing as an important regulator of mitochondrial function. 45 John T's study found that mTOR can regulate For personal use only.…”
mentioning
confidence: 99%
“…As a target of FoxOs, Tfeb regulates autophagosomal and lysosomal genes as well as the fusion of autophagosome with lysosome [96][97][98]. Tfeb activity is controlled by posttranslational modification, such as mTORC1 mediated phosphorylation that excludes Tfeb from the nucleus [99][100][101]. At transcriptional level, Tfeb gene was transactivated by FoxO1, which might account for mitophagy regulation and white-beige adipose tissue conversion [95].…”
Section: Foxo Transcription Factors In Mitochondrial Autophagymentioning
confidence: 99%